Perspectives on supporting Veterans' social needs during hospital to home health transitions: findings from the Transitions Nurse Program - Marguerite Daus; Marcie Lee; Lexus L. Ujano-De Motta; Ariel Holstein; Brianne Morgan; Karen Albright; Roman Ayele; Michaela McCarthy; Heidi Sjoberg; Christine D. Jones (BMC, 2024)
Abstract Background Veterans who need post-acute home health care (HHC) are at risk for adverse outcomes and unmet social needs. Veterans' social needs could be identified and met by community-based HHC clinicians due to their unique perspective from the home environment, acuity of Veterans they serve, and access to Veterans receiving community care. To understand these needs, we explored clinician, Veteran, and care partner perspectives to understand Veterans' social needs during the transition from hospital to home with skilled HHC. Methods Qualitative data were collected through individual interviews with Veterans Health Administration (VHA) inpatient & community HHC clinicians, Veterans, and care partners who have significant roles facilitating Veterans' hospital to home with HHC transition. To inform implementation of a care coordination quality improvement intervention, participants were asked about VHA and HHC care coordination and Veterans' social needs during these transitions. Interviews were recorded, transcribed, and analyzed inductively using thematic analysis and results were organized deductively according to relevant transitional care domains (Discharge Planning, Transition to Home, and HHC Delivery). Results We conducted 35 interviews at 4 VHA Medical Centers located in Western, Midwestern, and Southern U.S. regions during March 2021 through July 2022. We organized results by the three care transition domains and related themes by VHA, HHC, or Veteran/care partner perspective. Our themes included (1) how social needs affected access to HHC, (2) the need for social needs screening during hospitalization, (3) delays in HHC for Veterans discharged from community hospitals, and (4) a need for closed-loop communication between VHA and HHC to report social needs. Conclusions HHC is an underexplored space for Veterans social needs detection. While this research is preliminary, we recommend two steps forward from this work: (1) develop closed-loop communication and education pathways with HHC and (2) develop a partnership to integrate a social risk screener into HHC pathways.